2004
DOI: 10.1038/sj.gt.3302427
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic gene therapy of myeloproliferative disease developed in transgenic mice expressing P230 bcr/abl

Abstract: Antiangiogenic gene therapy offers an attractive approach to the treatment of a variety of malignancies, including those of the hematological system. However, evaluation of this approach has been hampered by the lack of appropriate animal models. We have recently produced transgenic mice expressing P230 bcr/abl that develop myeloproliferative disease (MPD) closely resembling human chronic myelogenous leukemia. Using this MPD murine model, we examined the feasibility of systemic antiangiogenic gene therapy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…41 In a recent study, it was reported that ES inhibited the progression of a myeloproliferative disorder in bcr/abl transgenic mice. 42 Retroviral gene therapy with combination of angiostatin and endostatin achieved responses in leukemic mice. 43 In clinical trials, antiangiogenic approaches targeting VEGF and VEGF receptors in AML have shown promising results as published recently.…”
Section: Spotlightmentioning
confidence: 99%
“…41 In a recent study, it was reported that ES inhibited the progression of a myeloproliferative disorder in bcr/abl transgenic mice. 42 Retroviral gene therapy with combination of angiostatin and endostatin achieved responses in leukemic mice. 43 In clinical trials, antiangiogenic approaches targeting VEGF and VEGF receptors in AML have shown promising results as published recently.…”
Section: Spotlightmentioning
confidence: 99%